Reactivity and effectiveness of traditional and novel ligands for multi-micronutrient fertilization in a calcareous soil - López-Rayo, Sandra; Nadal, Paloma; Lucena, Juan J. (Frontiers in Plant Science, 2015)
This study compares the effectiveness of multi-micronutrient formulations containing Fe, Mn, and Zn with traditional (EDTA, DTPA, HEEDTA, EDDHAm) or novel chelates (o,p-EDDHA, S,S-EDDS, IDHA) and natural complexing agents (gluconate and lignosulfonate). The stability and reactivity of the formulations were studied on batch experiments with calcareous soil and by speciation modeling. Formulations containing traditional ligands maintained higher Mn but lower Zn concentration in soil solution than the novel ligands. The gluconate and lignosulfonate maintained low concentrations of both Mn and Zn in soil solution. Selected formulations were applied into calcareous soil and their efficacy was evaluated in a pot experiment with soybean. The formulation containing DTPA led to the highest Zn concentration in plants, as well as the formulation containing S,S-EDDS in the short-term, which correlated with its biodegradability. The application of traditional or novel ligands in formulations did not result in sufficient plant Mn concentrations, which was related to the low Mn stability observed for all formulations under moderate oxidation conditions. The results highlight the need to consider the effect of metals and ligands interactions in multi-nutrient fertilization and the potential of S,S-EDDS to be used for Zn fertilization. Furthermore, it is necessary to explore new sources of Mn fertilization for calcareous soils that have greater stability and efficiency, or instead to use foliar fertilization.